2005
DOI: 10.1002/app.22888
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of novel biocidal cyclodextrin inclusion complexes grafted onto polyamide‐6 fabric by a redox method

Abstract: The synthesis of immobilized β‐cyclodextrin derivatives onto polyamide‐6 fabric is presented. These novel fabrics were prepared by graft‐copolymerization of glycidyl methacrylate (GMA) onto polyamide 6 fabric, using a chemical redox system K2S2O8/CuSO4·5H2O, followed by reaction of β‐cyclodextrins (CD) or monochlorotriazinyl (MCT β‐CD) with the GMA epoxy group. Some biocidal guests were complexed into CD cavity including p‐hydroxy benzoic acid, AgNO3–ethanolamine mixture, iodine, N,N‐diethyltoluamide (DETA), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…This indicated that the modification of PET nanofibers with CDP resulted in slightly higher thermal stability due to more energy requirement for decomposition of these samples having crosslinked structure. The increased thermal stability has been also observed for CD grafted polyamide 6 fabrics [38]. Moreover, the char yield was higher for PET/CDP nanofibers when compared to unmodified PET nanofibers possibly owing to the crosslinked CDP structure providing higher carbon residue upon burning.…”
Section: Thermal Characterization Of the Nanofibersmentioning
confidence: 69%
“…This indicated that the modification of PET nanofibers with CDP resulted in slightly higher thermal stability due to more energy requirement for decomposition of these samples having crosslinked structure. The increased thermal stability has been also observed for CD grafted polyamide 6 fabrics [38]. Moreover, the char yield was higher for PET/CDP nanofibers when compared to unmodified PET nanofibers possibly owing to the crosslinked CDP structure providing higher carbon residue upon burning.…”
Section: Thermal Characterization Of the Nanofibersmentioning
confidence: 69%
“…With these structural features, CDs are able to form host-guest complexes with hydrophobic molecules [3]. As a result of this function, the CDs have wide applications in textile function finishing [4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 98%
“…An antimicrobial agent (benzoic acid), an odour-producing compound (vanillin), and an insect repellent pesticide (N, N-diethyl-meta-toluamide (DEET)) were some of the chemicals investigated for inclusion in these bound cyclodextrins. [43][44][45] The unique ability of cyclodextrins to form reversible complexes with a range of chemicals makes them attractive in a number of polymer-bound applications, including drug delivery, odour removal and fragrance applications.…”
Section: Recent Studies On the Modification Of Textilesmentioning
confidence: 99%